2003
DOI: 10.1046/j.1423-0410.2003.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

The blood‐donation experience: perceived physical, psychological and social impact of blood donation on the donor

Abstract: The majority of effects elicited by blood donation on blood donors were positive (i.e. feelings of satisfaction, greater alertness, increased wellbeing, etc.). The positive effects did not differ from the negative regarding time of onset, yet their duration was reported to be significantly longer. There was no association between frequency of occurrence of positive effects and the number of blood donations, indicating that there is no 'addictive' relationship between donors and blood donations. The findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
75
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 32 publications
14
75
2
Order By: Relevance
“…As non-remunerated donated blood is the only blood source in Saudi Arabia, people’s motivation should be improved to keep the blood supply levels sufficient. Hence, more attempts should be made to attract society members for blood donation 25. In the present study, around half of the study sample reported a history of previous donation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As non-remunerated donated blood is the only blood source in Saudi Arabia, people’s motivation should be improved to keep the blood supply levels sufficient. Hence, more attempts should be made to attract society members for blood donation 25. In the present study, around half of the study sample reported a history of previous donation.…”
Section: Discussionmentioning
confidence: 73%
“…The factors influencing the individuals’ decision to give blood are a collection of individual specific observable characteristics, such as sociodemographic factors, and unobservable characteristics, such as the degree of altruism 4. Studies have been carried out to examine how blood donors differ from non-donors with respect to their socioeconomic and demographic characteristics, such as sex, age, marital status, ethnicity, levels of education and income 4,25,34,35. In the current study, male sex and levels of knowledge and attitude on blood donation were the significant predictors of the frequency of donation.…”
Section: Discussionmentioning
confidence: 99%
“…The important finding in this study, namely, high frequency of the positive long-lasting effect elicited in blood donors by blood donation is of great importance for the recruitment of new blood donors; there by blood donation can be made less frightening and perhaps even attractive. [16] In Lithuania, paid donors comprised 89.9% of the respondents. Research findings show that 93% of the paid donors give blood on a regular basis; while among the nonremunerated donors the same figure amounted to merely 20.6%.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, in the past three decades, studies continue to emerge from different countries, from developed[16] and developing,[713] probing the attitude and motivations of blood donors.…”
Section: Introductionmentioning
confidence: 99%